Estrogen Receptors Promote Migration, Invasion and Colony Formation of the Androgen-Independent Prostate Cancer Cells PC-3 Through β-Catenin Pathway - Lombardi, Ana Paola G.; Vicente, Carolina M.; Porto, Catarina S. (Frontiers in Endocrinology, 2020)
Prostate cancer is initially dependent on the androgen, gradually evolves into an androgen-independent form of the disease, also known as castration-resistant prostate cancer (CRPC). At this stage, current therapies scantily improve survival of the patient. Androgens and estrogens are involved in normal prostate and prostate cancer development. The mechanisms by which estrogens/estrogen receptors (ERs) induce prostate cancer and promote prostate cancer progression have not yet been fully identified. Our laboratory has shown that androgen-independent prostate cancer cells PC-3 express both ERα and ERβ. The activation of ERβ increases the expression of β-catenin and proliferation of PC-3 cells. We now report that the activation of ERβ promotes the increase of migration, invasion and anchorage-independent growth of PC-3 cells. Furthermore, the activation of ERα also plays a role in invasion and anchorage-independent growth of PC-3 cells. These effects are blocked by pretreatment with PKF 118-310, compound that disrupts the complex β-catenin/TCF/LEF, suggesting that ERs/β-catenin are involved in all cellular characteristics of tumor development in vitro. Furthermore, PKF 118-310 also inhibited the upregulation of vascular endothelial growth factor A (VEGFA) induced by activation of ERs. VEGF also is involved on invasion of PC-3 cells. In conclusion, this study provides novel insights into the signatures and molecular mechanisms of ERβ in androgen-independent prostate cancer cells PC-3. ERα also plays a role on invasion and colony formation of PC-3 cells.